Pengaruh Penggunaan Obat Khelasi Besi Terhadap Perubahan Kadar Ferritin Serum Pada Pasien Thalasemia Di Rumah Sakit Umum Daerah “X” Kota Bekasi - Agustiani, Elsya; Futihat, Chilyati Eky; Arianti, Anisa Rachmita; Maifitrianti, Maifitrianti (Jurnal Farmasi & Sains Indonesia, 2025)
Thalassemia is a blood disorder that is inherited from both parents to their children. Ferritin levels are often elevated due to repeated blood transfusions that cause iron buildup in the body, leading to serious complications if not treated with iron chelation therapy. Iron chelation is a therapeutic method to reduce excessive iron levels in the body that is not bound in plasma and excreted from the body. To see the effect of using iron chelation drugs on reducing serum ferritin levels in patients with thalassemia beta major. Analytical observational research with a retrospective cross-sectional study design using limited secondary medical record data. The sampling technique used consecutive sampling with the inclusion criteria of beta major thalassemia patients with serum ferritin levels ≥1000ng/mL who received a single iron chelation therapy treatment. The effect of iron chelation drug administration in beta major thalassemia patients on reducing serum ferritin levels was analyzed using the Wilcoxon Signed-Ranks Test. In this study, 50 patients met the inclusion criteria. 52% of patients were female, and 40% had an age range of 0-5 years. The most common single iron chelation drug was Deferasirox (85%), with a dose of 250 mg (49%). A total of 6% of patients had decreased serum ferritin levels (≥500ng/mL and <1000ng/mL). However, the results of the data analysis showed that there was no significant decrease in serum ferritin levels after single iron chelation. This study showed that single iron chelation therapy was effective in reducing serum ferritin levels, but not significant (p value>0.05).